Oxic and Anoxic Organic Polymer Degradation Potential of Endophytic Fungi From the Marine Macroalga, Ecklonia radiata - Perkins, Anita K.; Rose, Andrew L.; Grossart, Hans-Peter; Rojas-Jimenez, Keilor; Barroso Prescott, Selva K.; Oakes, Joanne M. (Frontiers in Microbiology, 2021)
Cellulose and chitin are the most abundant polymeric, organic carbon source globally. Thus, microbes degrading these polymers significantly influence global carbon cycling and greenhouse gas production. Fungi are recognized as important for cellulose decomposition in terrestrial environments, but are far less studied in marine environments, where bacterial organic matter degradation pathways tend to receive more attention. In this study, we investigated the potential of fungi to degrade kelp detritus, which is a major source of cellulose in marine systems. Given that kelp detritus can be transported considerable distances in the marine environment, we were specifically interested in the capability of endophytic fungi, which are transported with detritus, to ultimately contribute to kelp detritus degradation. We isolated 10 species and two strains of endophytic fungi from the kelp Ecklonia radiata. We then used a dye decolorization assay to assess their ability to degrade organic polymers (lignin, cellulose, and hemicellulose) under both oxic and anoxic conditions and compared their degradation ability with common terrestrial fungi. Under oxic conditions, there was evidence that Ascomycota isolates produced cellulose-degrading extracellular enzymes (associated with manganese peroxidase and sulfur-containing lignin peroxidase), while Mucoromycota isolates appeared to produce both lignin and cellulose-degrading extracellular enzymes, and all Basidiomycota isolates produced lignin-degrading enzymes (associated with laccase and lignin peroxidase). Under anoxic conditions, only three kelp endophytes degraded cellulose. We concluded that kelp fungal endophytes can contribute to cellulose degradation in both oxic and anoxic environments. Thus, endophytic kelp fungi may play a significant role in marine carbon cycling via polymeric organic matter degradation.